Mobile network interconnection and investments - Tobias Veith (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Abstract In markets with competing interconnected networks like mobile telecommunication markets investments affect the investor's and also any competitors' profits. In a theoretical model it is shown that cost-reducing investments reduce the investor's termination rates and increase competitors' termination rates under the callingparty- network-pays regime. Moreover, investments increase off-net traffic from the investor's network but also from competitors' networks. Regulation changes the effect on competitors' termination rates but all other effects remain the same or are strengthened. Empirical results support the theoretical findings concerning the investor's termination rates and the findings on off-net traffic. Competitors' termination rates decrease. The negative termination rate effect even outweighs the quantity effect in the competitors' profit functions. Testing for a common regulation-investment effect provides evidence that the negative investment externality is not due to regulation.
Keywords: L51; L52; L86; L96; O31; O33; 330; regulation; mobile telecommunications; investments; interconnection; Mobilkommunikation; Investition; Telekommunikationsnetz; Netzzugang; Telekommunikationsgebühr; Wettbewerb; Theorie